Changes in Marriage Age Limits and Marriage Dispensations: A Study of Causes and Impacts on the Religious Courts in North Sulawesi - Mursyid, Salma; Yusuf, Nasruddin (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2022)
This study aimed to analyze the impact of the enactment of Law Number 16 of 2019, the causes of the application for marriage dispensations, and the judge’s reasons for the marriage dispensation grant. This research was necessary due to the establishment of Law Number 16 of 2019 concerning amendments to Law Number 1 of 1974 regarding Marriage—which aims for equality in the minimum age limit in marriage, namely 19 for both men and women—that increases the number of applications for marriage dispensations in Religious Courts. This study is empirical legal research with a phenomenological approach. The study found that the law’s enactment brought some positive impacts, such as protection of the rights of minors, assurance of physically and mentally healthy offspring (as a result of maturely married couples), reduction of women’s vulnerability to domestic violence, and suppression of marital problems. On the other hand, however, this law caused an increase in the application for marriage dispensations at all Religious Courts in North Sulawesi. Meanwhile, reasons for marriage dispensation requests included pregnancy out of wedlock, the influence of local customs/traditions, economic concerns, parents’ will for child marriage, parents’ effort in preventing their children from acts contrary to religious norms, uncontrolled socializing, and elderly parents’ property bequeathment. Regarding the judge’s judgment in granting marriage dispensations, considerations were made on a case-by-case basis. In conclusion, the law distinguishing the minimum age of marriage between men and women should be non-existent because it will only hinder the fundamental rights or constitutional rights of every citizen, as guaranteed in Article 28B paragraphs (1) and (2) of the Indonesian Constitution.